2021
DOI: 10.1371/journal.pone.0246273
|View full text |Cite
|
Sign up to set email alerts
|

A Delphi study to explore and gain consensus regarding the most important barriers and facilitators affecting physiotherapist and pharmacist non-medical prescribing

Abstract: Non-medical prescribing was introduced into the United Kingdom to improve patient care, but early research indicated a third of Allied Health Professionals may not use their prescribing qualification. A previous literature review, highlighting factors influencing prescribing, identified only papers with nursing and pharmacy participants. This investigation explored consensus on factors affecting physiotherapist and pharmacist non-medical prescribers. A three round Delphi study was conducted with pharmacist and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…We followed-up with non-respondents and conducted both rounds of data collection shortly after each other. This resulted in a relative low attrition of 19% between the two rounds [ 25 , 31 ]. Anonymity was granted throughout the data collection process to encourage creativity and to promote inclusive views.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We followed-up with non-respondents and conducted both rounds of data collection shortly after each other. This resulted in a relative low attrition of 19% between the two rounds [ 25 , 31 ]. Anonymity was granted throughout the data collection process to encourage creativity and to promote inclusive views.…”
Section: Discussionmentioning
confidence: 99%
“…Anonymity is an essential feature to avoid conformity and social pressure [ 24 ]. The Delphi technique has become a well-established tool in (global) health research [ 19 , 25 28 ]. Mulligan et al [ 29 ] demonstrated that it is a useful tool for gathering views on research priorities and impact valuations in global health research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in barriers encountered by the two models appears to point to the influence of context (both organizational context and the context of the individual medication) on implementation outcomes. In a recent Delphi study a significant number of initial barrier statements were identified, however only one was able to reach consensus, also supporting the influence of context on perceived implementation barriers (Graham-Clarke et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review described 15 factors or themes that had the potential to influence the implementation of prescribing by non-medical professions [14]. It was noted that the majority of the included studies focused on prescribing by nurses, with the remainder addressing prescribing by pharmacists.…”
Section: Introductionmentioning
confidence: 99%